Jukola: Democratic Music Choice in a Public Space - O'Hara, Kenton; Lipson, Matthew; Jansen, Marcel; Unger, Axel; Jeffries, Huw; Macer, Peter (ACM - Association for Computing Machinery, 2004)
Jukola is an interactive MP3 Jukebox device designed to allow a group of people in a public space to democratically choose the music being played. A public display is used to nominate songs which are subsequently voted on by people in the bar using networked wireless handheld devices. Local bands and artists can also upload their own MP3s to the device over the Web. The paper presents a field trial of the system in a local café bar. As well as the value in affording a democratic musical outcome, more importantly the whole process of voting and choice created a rich source of social value and interaction in the form of discussions around music, playful competition, identity management and sense of community.